2017
DOI: 10.1177/1535370217693115
|View full text |Cite
|
Sign up to set email alerts
|

Featured Article: Chemotherapeutic delivery using pH-responsive, affinity-based release

Abstract: Impact statementDoxorubicin (DOX) is especially cytotoxic to the heart, liver, kidneys, and healthy tissues surrounding the tumor microenvironment. This systemic toxicity can be partially addressed by local, tumor-specific drug delivery systems. While pH-sensitive DOX delivery systems have been developed by several other groups, many lack a prolonged and consistent release profile required to successfully treat heterogeneous tumors. Our system of a chemically modified form of DOX combined with an affinity-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In the case of tumor microenvironments, the slightly acidic tumor conditions are attributed to the elevated metabolism and proliferation of tumor cells. Another method used to achieve site‐specific delivery of drugs in mildly acidic conditions involves the incorporation of an acid‐labile hydrazone bond in the backbone of the drug …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of tumor microenvironments, the slightly acidic tumor conditions are attributed to the elevated metabolism and proliferation of tumor cells. Another method used to achieve site‐specific delivery of drugs in mildly acidic conditions involves the incorporation of an acid‐labile hydrazone bond in the backbone of the drug …”
Section: Introductionmentioning
confidence: 99%
“…Another method used to achieve site-specific delivery of drugs in mildly acidic conditions involves the incorporation of an acid-labile hydrazone bond in the backbone of the drug. 12,27,29,31,34 Building upon the success of thermoresponsive and pHresponsive delivery systems, some groups have combined these two stimuli to develop dual-stimuli responsive delivery systems. [11][12][13][14][15][16][17] The benefit of such dual-responsive delivery systems is that the stimuli synergistically work together to modulate drug release.…”
Section: Introductionmentioning
confidence: 99%
“…[22,23] Our polymers may allow for the exploration of formulations with new rheological properties while sustaining release of relevant pharmacological agents or have the release triggered by an endogenous or exogenous stimuli. [35] Similar work has been done in the design of small conjugates for environmental water treatment and found preferential loading of active pharmaceutical ingredients from certain crosslinkers over others. [36,37] This preferential loading may be a factor of molecular recognition provided by the cyclodextrin to crosslinker combination or alternatively, by an alteration of the thermodynamic parameters that drive the complexation behavior.…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, the identification of key descriptors and the use of predictive software could lead to new chemistries for extending drug delivery. Beyond using the traditional adamantane-CD bond for improved drug delivery [46,50], recent work has shown that molecular tethering of multiple drug molecules can improve interactions with CD-based polymers [51]. Specifically, the delivery window for rapamycin, traditionally a quickly-diffusing and relatively insoluble drug, was tripled to 65 days of release in a "dimeric" formulation versus the standard drug molecules, while maintaining antifibrotic activity [51].…”
Section: Discussionmentioning
confidence: 99%